(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Some vital statistics of the population of Portunus spinicarpus inhabiting the Golfo de Salamanca, Colombian Caribbean, are presented for the first time. Condition factor was found stable the year round, Von Bertalanffy growth parameters were estimated as L∞=38.6 mm, K= 2.5 year-1, to= -0.0573 year. Natural mortality was estimated as 4.62 year-1. P. spinicarpus seem to prefer deep waters and sand-muddy bottoms.